Multikulturalizem v kontekstu migracij - Milharčič-Hladnik, Mirjam (Knjižnica, 2009)
Multiculturalism is a new theoretical and political concept which emerged thirty years ago and which has been in the focus of modern discussions about intercultural dialogue, societies and migrations. The article stresses that migrations are as old as the human race so they have been the basis of social order and intercultural relations. Some examples of relations based either on conflicts or on a dialogue are given. Thus, the controversy of multiculturality in social and political perspective is explained. All modern countries have to be concerned with the phenomenon of multiculturalism although they deny its existence. It is necessary to consider the way of life and the needs of people who are different from the majority of the society. Those people have their own way of life and identity which is different from the "national" one.
Keywords: multikulturalizem; migracije; human migration; medkulturno sporazumevanje